NO2 hotspots: Are we measuring in the right places?. (April 2019) - Beckwith, Michael; Bates, Elizabeth; Gillah, Andrew; Carslaw, Nicola
Abstract: Nitrogen Dioxide (NO2 ) is a major atmospheric pollutant which is produced from a variety of anthropogenic sources, notably vehicular emissions. High NO2 concentrations are found in and around the urban environment and as such pose a significant threat to human health. Diffusion tube surveys of NO2 concentrations were carried out at a variety of intersections and road layouts over a 3-month period in 2017. This study identified that 'hotspots' in NO2 concentrations frequently occurred in sections of road where vehicles are accelerating or queueing. Under these conditions, concentrations were elevated by 58.6% and 52.6% respectively compared to when vehicles were cruising. Analysis of environmental factors which influence NO2 concentrations show that meteorology, topography, traffic volume and driver behaviour all contribute. The results highlight the complexity of monitoring hotspot locations and show the need for traffic and driver behaviour to be included in vehicle emission models. Additionally, the investigation suggests need for caution when relying on in-situ monitors to determine pollutant exceedances as there is shown to be substantial variation along a street and the location of the monitor is critical. Highlights: Road-side monitoring of nitrogen dioxide concentrations at a variety of intersections. Assessment of road intersection traffic behaviour, environmental variables and impact on nitrogen dioxide concentrations. Comparison of nitrogen dioxide concentrations at road junctions against in-situ monitors.